Stress and Coping Strategies among the Caregivers of the Patients Admitted in Critical Care Units in Tertiary Hospital - Thapa, Saroja; Pandey, Prabin Raj (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: The number of patients with higher severity of illness admitted to critical care units has increased in recent years. Family members of the patients suffer physiological, emotional, and psychological changes in addition to financial and organizational losses. Those who struggle with efficient coping may experience interpersonal difficulties and struggle to find solutions to those issues. The aim of this study was to explore the stress and coping strategies among the caregivers of the patients admitted in critical care units. Methods: A purposive phenomenological study involving eight caregivers from Intensive Care Unit and High Dependency Unit was conducted, using in-depth interview. Data was collected between August to September 2024. Ethical clearance was obtained from the Institutional Review Committee (Reference number: NAPFH-008/2024). The interviews were audio-recorded, transcribed verbatim, translated in English and analysed using thematic analysis. Results: Out of eight participants, ten themes were identified. These include: a) Lack of information and communication; b) Emotional response to ICU and HDU admission; c) Role strain and physical exhaustion; d)Financial strain; e) Experience of the Critical Care Unit (CCU); f) Seeking Social Support; g) Emotional Regulation and Acceptance; h) Coping Mechanisms; i) Communication and Trust in Healthcare Providers; and j) Maintaining Physical Health. Conclusions: The study found that family members experienced stress in their role as caregivers. People’s perception of stress had a big impact on the caregiving duties they carry out. The findings showed that coping strategies were implied according to the stress perceived by the family members as caregivers.